EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DAN THINKING ALOUD PAIRS PROBLEM SOLVING (TAPPS) PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI SIKAP PERCAYA DIRI SISWA SMPN KABUPATEN SUKOHARJO - Maghfiroh Yanuarti; Budi Usodo; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objective of this research was to investigate the effect of the learning models on the learning achievement in Mathematics viewed from the self confidence of the students. The learning models compared were Think Pair Share (TPS)  model, Thinking Aloud Pairs Problem (TAPPS) model, and conventional model. This research was the quasi-experimental research with 3×3 factorial design. The population of the research was all students of Junior High School (SMP) in Sukoharjo. The samples were chosen by using stratified cluster random sampling. The samples were 302 students; consisted of 100 students in the first experimental class, 101 in the second experimental class, and 101 students in control class. The instruments used to collect the data were the test of mathematics achievement and questionnaire of self confidence. Pre-requisite tests were used Lilliefors method for normality test and Bartlett method for homogeneity test. After examining the data, it showed that the data had same variance and they were in normal distribution. Prior knowledge data are examined by using one-way ANOVA with unbalanced cells. It showed that three classes had balance prior knowledge. Meanwhile, the technique of analyzing the data was two-ways ANOVA with unbalanced cells. The result of research showed that: (1) TPS model had better learning achievement than TAPPS model and conventional model, TAPPS model had better learning achievement than conventional model. (2) the students having high self confidence had better learning achievement than those having medium and low self confidence, the students having medium and low self confidence had equally mathematics learning achievement. (3) there was an interaction the aforementioned learning models and the categories of the self confidence on the learning achievement in Mathematics of the student.Keywords:Think Pair Share (TPS), Think Aloud Pairs Problem Solving (TAPPS), mathematics learning achievement, and self confidence.